Penerapan Sistem Digital Berbasis Online bagi UMKM Studi Kasus Kana Shibori - Erizal Erizal; Wiji Nurastuti (Jurnal Dinamika Informatika, 2021)
Micro, Small and Medium Enterprises (MSMEs) play a major role in supporting Indonesia's national economy, proven to contribute 60.34% of Gross Domestic Product (GDP) before the Covid-19 pandemic in 2020. The role of MSMEs needs to be further enhanced, especially in the midst of a pandemic. as it is now. The steps or processes taken for MSME actors are directed at efforts to improve product quality, which in the end is expected to increase the competitiveness of MSME products. Utilization of information technology is a very appropriate choice for efficiency and improvement of digital product management, data processing, and information systems for MSMEs in Yogyakarta City. The final output from the use of this technology can support the implementation of digital marketing for MSME products in a better and more targeted manner.